Lead accumulation and its histological impact on Cymodocea serrulata seagrass in the laboratory - Dwi Rosalina; Endang Yuli Herawati; Muhammad Musa; Dini Sofarini; Mohammad Amin; Yenny Risjani (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of this study was to determine the concentration of lead (Pb) in Cymodocea serrulata tissues (roots, rhizomes, and leaves) using the AAS method, also to figure out Pb’s impact on seagrass’ histology and elements using the SEM-EDX Mapping method. The results showed that the higher the concentration and the length of the planting period, the higher the accumulation of heavy metals in the seagrass tissues. In this study, Pb was largely accumulated in the leaves, roots, and rhizomes tissue. Moreover, the seagrass histology in the epidermis and endodermis underwent shape and structure changes; it also went through damage or thickening at 15 ppm concentration, compared to control. This study strengthens the usefulness and relationship of Cymodocea serrulata seagrass as a biological indicator of metal contamination in the waters.